2017
DOI: 10.1371/journal.pone.0178375
|View full text |Cite
|
Sign up to set email alerts
|

The MTH1 inhibitor TH588 demonstrates anti-tumoral effects alone and in combination with everolimus, 5-FU and gamma-irradiation in neuroendocrine tumor cells

Abstract: Modulation of the redox system in cancer cells has been considered a promising target for anti-cancer therapy. The novel MTH1 inhibitor TH588 proved tremendous potential in terms of cancer cell eradication, yet its specificity has been questioned by recent reports, indicating that TH588 may also induce cancer cell death by alternative mechanisms than MTH1 inhibition. Here we used a panel of heterogeneous neuroendocrine tumor cells in order to assess cellular mechanisms and molecular signaling pathways implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…As mentioned above, independent groups have confirmed cytotoxic effects of TH588 in several studies [ 7 , 13 ]. Some studies have also identified MTH1 inhibitors with similar or even lower IC50 [ 13 , 25 ] which either caused cytotoxic effects regarded as MTH1 independent or had no significant impact on cell viability thus challenging the concept of MTH1 inhibition as an anti-tumor strategy.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…As mentioned above, independent groups have confirmed cytotoxic effects of TH588 in several studies [ 7 , 13 ]. Some studies have also identified MTH1 inhibitors with similar or even lower IC50 [ 13 , 25 ] which either caused cytotoxic effects regarded as MTH1 independent or had no significant impact on cell viability thus challenging the concept of MTH1 inhibition as an anti-tumor strategy.…”
Section: Discussionmentioning
confidence: 74%
“…Consequently, targeting this enzymatic function has been proposed to induce single strand breaks and G:C to T:A transversion mutations during DNA replication [ 5 ]. The MTH1 inhibitor TH588 was identified by Gad and co-authors in 2014 [ 6 ] and has been used in several studies subsequently [ 7 9 ]. Other investigators have generated inhibitors independently as reviewed very recently [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is of vital importance to pediatric glioblastoma patients, whose main treatment-option is ionizing radiation. An increased response to ionizing radiation in TH588-treated neuroendocrine tumor cell lines has recently been reported by Prada et al [ 50 ]. In contrast to the glioblastoma cell lines, the MTH1 inhibitor failed to affect the clonogenic survival of irradiated fibroblasts.…”
Section: Discussionmentioning
confidence: 76%
“…On top of the MTH1 inhibition, alternative mechanisms of TH588 have been reported as its anti-cancer effects including tubulin depolymerization and AKT signaling downregulation [ 32 , 33 ]. To confirm it, we investigated the spindle morphology of mitotic cells upon treatment of 5 and 10 µM of TH588.…”
Section: Resultsmentioning
confidence: 99%